PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PERSEDIAAN DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS - Fajriyanti, Nurul; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2024)
The phenomenon of declining profitability of manufacturing companies from 2018-2020 causes investors to need to know the company's activities through the working capital turnover ratio, inventory turnover, accounts receivable turnover. Therefore, this study aims to determine the effect of working capital turnover, inventory turnover, accounts receivable turnover on profitability in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The method applied to process research data is a quantitative-descriptive method with data from the financial statements of the manufacturing sector from 2018-2020. From the results of multiple regression analysis using SPSS 25.0, it is known that working capital turnover has a significant negative effect on profitability. Meanwhile, inventory turnover has no significant negative effect on profitability. Accounts Receivable Turnover has no significant positive effect on profitability.